Efisiensi Perencanaan Anggaran Di Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung Tahun Anggaran 2019-2021 - Ilsan Masdrian; Asep Hidayat; Ibnu Malik (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The process that becomes an impediment in budget absorption is due to inadequate budget planning at the Bandung City Fire and Disaster Management Office, budget absorption varies and is still weak in carrying out efficiency. The goal of this study is to assess the Bandung City Fire and Disaster Management Departement efficiency in carrying out budget planning utilizing the dimensions of budget policy formulation and budget operational planning, and it can also be utilized as evaluation material in budget planning efficiency. The method used in this research is a qualitative approach and the type of research is descriptive. Primary and secondary data sources were used in gathering data utilizing a purposive sample strategy using information based on people who contribute information based on experience and expertise. The Miles and Hubberman approach was utilized in data analysis, comprising the steps of data reduction, data display, and generating conclusions. According to the findings of this study, the Bandung City Fire and Disaster Management Office's budget planning efficiency could not be optimized.Keyword : Efficiency, Planning, Budget